A 1‐Hydroxy‐1H‐imidazole ESIPT Emitter Demonstrating anti‐Kasha Fluorescence and Direct Excitation of a Tautomeric Form. Issue 10 (14th October 2021) - Shekhovtsov, Nikita A.; Nikolaenkova, Elena B.; Berezin, Alexey S.; Plyusnin, Victor F.; Vinogradova, Katerina A.; Naumov, Dmitry Yu.; Pervukhina, Natalia V.; Tikhonov, Alexsei Ya.; Bushuev, Mark B.
Abstract: The ability of 1‐hydroxy‐1 H ‐imidazoles to exist in the form of two prototropic tautomers, the N‐hydroxy and the N‐oxide forms, can be utilized in the design of new types of ESIPT‐fluorophores (ESIPT=excited state intramolecular proton transfer). Here we report the first example of 1‐hydroxy‐1 H ‐imidazole‐based ESIPT‐fluorophores, 1‐hydroxy‐5‐methyl‐2, 4‐di(pyridin‐2‐yl)‐1 H ‐imidazole (HL ), featuring a short intramolecular hydrogen bond O−H⋅⋅⋅N (O⋅⋅⋅N 2.56 Å) as a pre‐requisite for ESIPT. The emission of HL originates from the anti‐Kasha S2 →S0 fluorescence in the N‐oxide form as a result of a large S2 –S1 energy gap slowing down the S2 →S1 internal conversion. Due to an energy barrier between the N‐hydroxy and N‐oxide forms in the ground state, the HL molecules can be trapped and photoexcited in the N‐oxide form leading to the Stokes shift of ca . 60 nm which is the smallest among known ESIPT‐fluorophores. Abstract : The first example of 1‐hydroxy‐1 H ‐imidazole‐based ESIPT‐fluorophores demonstrates the anti‐Kasha S2 →S0 fluorescence, whereas the S1 state decays non‐radiatively via a S0 /S1 conical intersection. The energy barrier between the N‐hydroxy (normal) and the N‐oxide (tautomeric) forms in the ground state allows trapping and excitation of the HL molecules in the N‐oxide form leading to the smallest Stokes shift among known ESIPT‐fluorophores ( ca . 60 nm).